Peningkatan Kesadaran dan Pengetahuan tentang Penyakit Periodontal pada Pasien Diabetes Melitus di Puskesmas Bara-Barayya - Zahrawi Astrie Ahkam; Hasrini Hasrini; Amirah Maritsa; Arfiah Jauharuddin; Dewi Sartika (MENGABDI : Jurnal Hasil Kegiatan Bersama Masyarakat, 2023)
Periodontal disease is a complication that often occurs in diabetes mellitus (DM) patients. This disease can worsen the patient's general health condition. This community service aims to increase awareness and knowledge about periodontal disease in DM patients at the Bara-Barayya Health Center. The methods used include counseling, dental and oral health checks, and distribution of educational leaflets. The results of the activity showed a significant increase in the knowledge and awareness of DM patients regarding the importance of maintaining oral health. It is hoped that this will help in the prevention and management of periodontal disease in DM patients.